Self-transfecting GMO-PMO chimera targeting Nanog enable gene silencing in vitro and suppresses tumor growth in 4T1 allografts in mouse - Ujjal Das; Jayanta Kundu; Pallab Shaw; Chandra Bose; Atanu Ghosh; Shalini Gupta; Sudipta Sarkar; Jhuma Bhadra; Surajit Sinha (Elsevier, 2023)
Phosphorodiamidate morpholino oligonucleotide (PMO)-based antisense reagents cannot enter cells without the help of a delivery technique, which limits their clinical applications. To overcome this problem, self-transfecting guanidinium-linked morpholino (GMO)-PMO or PMO-GMO chimeras have been explored as antisense agents. GMO facilitates cellular internalization and participates in Watson-Crick base pairing. Targeting NANOG in MCF7 cells resulted in decline of the whole epithelial to mesenchymal transition (EMT) and stemness pathway, evident through its phenotypic manifestations, all of which were promulgated in combination with Taxol due to downregulation of MDR1 and ABCG2. GMO-PMO-mediated knockdown of no tail gene resulted in desired phenotypes in zebrafish even upon delivery after 16-cell stages. In BALB/c mice, 4T1 allografts were found to regress via intra-tumoral administration of NANOG GMO-PMO antisense oligonucleotides (ASOs), which was associated with occurrence of necrotic regions. GMO-PMO-mediated tumor regression restored histopathological damage in liver, kidney, and spleen caused by 4T1 mammary carcinoma. Serum parameters of systemic toxicity indicated that GMO-PMO chimeras are safe. To the best of our knowledge, self-transfecting antisense reagent is the first report since the discovery of guanidinium-linked DNA (DNG), which could be useful as a combination cancer therapy and, in principle, can render inhibition of any target gene without using any delivery vehicle.